The Growing Burden of School Adolescent Hypertension in North Kordofan, Sudan, A Call for School-Based Interventions - Mohammed, Sara Ismail; Mohammed, Sujood Ismail; Mahjoub, Yasir (British Journal of Healthcare and Medical Research, 2025)
-